Women and Employment - Rajat Sharma (Jaipur Black and Black Publishing Corporation, 2023)
women rights; constitution and Indian women; how to select your Carrer how to plan for career how to plan for career preparing for well-paid job developing entrepreneurial skills; principles of career planning our personality and its development role of personality in job; how to make better personality? how to choose better job? tips of writing effective resume how to write best biodata? application for job through internet. Job application form. Essential needs for getting a job. Discover the best job.
Keywords: Groups of people